The relation between physical and mental load, and the course of physiological functions and cognitive performance - Fiľo, Petr; Janoušek, Oto (Theoretical issues in ergonomics science, 2022)
The objective of our study was to investigate differences in cognitive performance connected with physical load of varying intensities. One half of 88 examined persons sat on office chairs, and the other half sat on chairs with the added modification of the gymnastic (Swiss) ball called the dynamic directional seat pad (pad). The first rest phase was followed by the load phase, in which the subjects were administered a 20-minute sustained attention test. The number of correct answers and errors was evaluated. A BIOPAC apparatus continually recorded thoracic respiration, electrodermal activity, finger temperature, heart rate, and heart rate variability. Females on pads made 58% fewer errors than females on chairs; the number of errors was closely related to the depth of their breathing (tidal volume). It was found out that the use of the pad, in addition to the already known health benefits, also brings an increase in the precision of cognitive performance. LIST OF ABBREVIATIONS